PRAKTISI NOTARIS SEBAGAI PENGAJAR UNTUK MELAHIRKAN LULUSAN YANG MUMPUNI KAITANNYA DENGAN PROGRAM MBKM - Benny Djaja (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
One of the requirements for Public Notary appointment according to UUJN is the completion of a graduate studyprogram in notary education. The growing number of universities of ering the Notary Masters Study Program(MKn) gives rise to some problems: the absence of curriculum standards, the lack of competence of the teachingstaf s to produce professional Notaries, and the increasing number of graduates not in proportion to the availablequota for new appointments. Making available adequate legal instruments and professionals in accordance with thewritten regulations to respond to the needs of the community requires good cooperation between legal institutionsand education institutions, in this case particularly the MKn program. The elaborations in this writing aims tounderstand the responsibilities of notary as public of icer especially in light of the Professional OrganizationRegulation, as well as the necessity to incorporate practitioners as part of the lecturers board in the MKn StudyProgram, in line with the Government program Merdeka Belajar, Kampus Merdeka (MBKM). MKn Program aimsto produce professional and competent Notary candidates pursuant to the Notary Association Regulation. Followingtheir graduation, ef orts to achieve said aims are resumed through the obligations of prospective notaries toparticipate in individual internship, communal internship, as well as seminars/ conferences and socializations.Hereunder, the authors describe a community service activity carried out in the form of empowerment andsocialization, targeted to improve the understanding of candidate notaries in an event called Special MembersSelection Briefing organized by the West Jakarta Regional Management of the Indonesian Notary Association.Following the dissemination of materials concerning Notaries as part of the legal profession and a public of icerpursuant to UUJN, Notaries as professional educator within Prodi MKn, and their responsibilities, these activitiesare wrapped up with a Q&A session and evaluation. The intended outcome of these activities are scientificpublications in an ISSN-registered journal and a selected mass media outlet. Â ABSTRAK: Persyaratan untuk dapat diangkat menjadi Notaris sesuai dengan UUJN salah satunya yaitu telah menyelesaikanpendidikan spesialis Kenotariatan. Banyaknya Perguruan Tinggi penyelenggara program studi MagisterKenotariatan (Prodi MKn) menimbulkan permasalahan, antara lain tidak adanya standar kurikulum, kurangnyakompetensi pengajar untuk melahirkan Notaris yang profesional, dan meningkatnya jumlah lulusan pendidikanNotaris yang tidak seimbang dengan jumlah formasi pengangkatan Notaris. Untuk mendukung terciptanya perangkatatau profesi hukum yang sesuai dengan aturan tertulis dan menjawab kebutuhan masyarakat, diperlukan kerjasamayang harmonis antara institusi hukum dengan lembaga pendidikan hukum, yaitu Prodi MKn. Penelitian ini bertujuanuntuk memahami pertanggungjawaban Notaris sebagai pejabat publik, khususnya terkait Peraturan PerkumpulanNotaris, dan pentingnya kehadiran praktisi Notaris sebagai bagian dari tim pengajar di Prodi MKn sesuai dengantujuan program Merdeka Belajar Kampus Merdeka (MBKM) yang dicanangkan Pemerintah untuk perguruan tinggi.Prodi MKn bertujuan untuk membentuk calon Notaris yang profesional dan mempunyai kompetensi mumpunisesuai dengan Peraturan Perkumpulan organisasi Notaris, yaitu Ikatan Notaris Indonesia (INI). Pasca kelulusan,tujuan tersebut dilanjutkan melalui kewajiban magang (perorangan), magang bersama, serta mengikutiseminar/penyuluhan hukum. Dalam tulisan ini, Penulis menguraikan pelaksanaan pengabdian masyarakat dalambentuk penyuluhan dan sosialisasi untuk meningkatkan pemahaman para calon Notaris dalam Pembekalan SeleksiAnggota Luar Biasa Wilayah Jakarta Barat. Setelah pemberian materi mengenai Notaris sebagai bagian dari profesihukum dan pejabat publik sesuai dengan UUJN, Notaris sebagai pendidik profesional dalam Prodi MKn, dantanggung jawab Notaris, kegiatan ini diakhiri dengan tanya jawab dan evaluasi. Rencana luaran yang dihasilkan darikegiatan ini berupa publikasi ilmiah pada jurnal ber-ISSN dan media massa.